Learning Neo4j : run blazingly fast queries on complex graph datasets with the power of the Neo4j graph database - Bruggen, Rik van (Community experience distilled., 2014)
This book is for developers who want an alternative way to store and process data within their applications. No previous graph database experience is required; however, some basic database knowledge will help you understand the concepts more easily.